Assessment of the Progress of Rural Women through Self Help Groups Development in Haryana - Kumari, Neelam; Malik, Joginder Singh (Indian Journal of Extension Education, 2020)
The success of the Indian experience regarding Self Help Groups (SHGs) helped in realizing that the rural people are able to save and capable enough to repay the loans in time and open ups the potential markets for formal financial institutions. SHGs had been crucial elements in increasing economic opportunities and empowerment. The study was conducted in Bhiwani District of Haryana with 120 respondents. The study revealed that majority of the respondents were young aged, illiterate followed by matriculation level of education, having medium family size, living as nuclear families and the average annual family income was above Rs. 2 lakhs. Majority of the respondents were in contact with the gram pradhan/local leaders and SHG officers/workers. For gaining information, majority of the respondents were seeking help from watching television, and family members followed by internets. Majority of the respondents (91.70%) were involved in preparing products round the year and majority of the respondents (66.70%) were selling their products or providing their services to consumers through individual sale. The majority of the respondents (52.50%) were medium risk takers. The major problems faced by the respondents in effective functioning were: price problems, delay in getting loans, improper demand and supply chain of commodities, marketing of products and transportation.
Keywords: Empowerment; Income; Problems; Self help group; Women